Perinatal features of children with Silver-Russell syndrome due to 11p15 loss of methylation - Darneau, Diane; Giabicani, Eloïse; Netchine, Irène; Pham, Aurélie (Frontiers in Pediatrics, 2024)
Background A diagnosis of Silver–Russell syndrome (SRS), a rare imprinting disorder responsible for foetal growth restriction, is considered for patients presenting at least four criteria of the Netchine-Harbison clinical scoring system (NH-CSS). Certain items of the NH-CSS are not assessable until the age of 2 years. The objective was to determine perinatal characteristics of children with SRS to allow an early diagnosis. Methods We retrospectively compared the perinatal characteristics of children with SRS (n = 17) with those of newborns small for gestational age (SGA) due to placental insufficiency (PI) (n = 21). Results Children with SRS showed earlier and more severely altered foetal biometry than SGA newborns due to PI. Twenty-three percent of patients with SRS showed uterine artery Doppler anomalies. SRS children were significantly smaller at birth (birth length <-3 SDS in 77% of cases in the SRS group vs. 15% in the PI group, p = 0.0001). Conclusion The diagnosis of SRS must be evoked in the neonatal period for SGA newborns with a growth delay present from the second trimester of pregnancy, a birth length <-3 SDS and a relative macrocephaly. Doppler anomalies, classically used to orient the cause of SGA towards PI, did not rule out the diagnosis of SRS.